Induced Cognitive Impairments Reversed by Grafts of Neural Precursors: A Longitudinal Study in a Macaque Model of Parkinson's Disease. Issue 10 (9th February 2022) - Wianny, Florence; Dzahini, Kwamivi; Fifel, Karim; Wilson, Charles Robert Eden; Bernat, Agnieszka; Dolmazon, Virginie; Misery, Pierre; Lamy, Camille; Giroud, Pascale; Cooper, Howard Michael; Knoblauch, Kenneth; Procyk, Emmanuel; et al.
Abstract: Parkinson's disease (PD) evolves over an extended and variable period in humans; years prior to the onset of classical motor symptoms, sleep and biological rhythm disorders develop, significantly impacting the quality‐of‐life of patients. Circadian‐rhythm disorders are accompanied by mild cognitive deficits that progressively worsen with disease progression and can constitute a severe burden for patients at later stages. The gold‐standard 6‐methyl‐1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridin (MPTP) macaque model of PD recapitulates the progression of motor and nonmotor symptoms over contracted periods of time. Here, this multidisciplinary/multiparametric study follows, in five animals, the steady progression of motor and nonmotor symptoms and describes their reversal following grafts of neural precursors in diverse functional domains of the basal ganglia. Results show unprecedented recovery from cognitive symptoms in addition to a strong clinical motor recuperation. Both motor and cognitive recovery and partial circadian rhythm recovery correlate with the degree of graft integration, and in a subset of animals, with in vivo levels of striatal dopaminergic innervation and function. The present study provides empirical evidence that integration of neural precursors following transplantation efficiently restores function at multiple levels in parkinsonian nonhuman primates and, given interindividuality of disease progression and recovery, underlines the importance of longitudinal multidisciplinary assessments in view of clinical translation. Abstract : This paper shows that successful engraftment of neural precursors restore function at multiple levels in parkinsonian monkeys. Recovery of motor symptoms is accompanied by unprecedented recovery of cognitive performances and chronobiological rhythms and by increased in vivo levels of striatal dopaminergic innervation (dopaminergic transporters).